O germinar do Pinheirinho dos Palmares: etnografia das relações entre removidos, movimento social e Estado - Barretti, Fabricio dos Santos (2018)
Exactly one month from completing five years since the Pinheirinho’s eviction, 1.461 of the 1.750 evicted families received the keys to their houses on Pinheirinho dos Palmares II, neighborhood built exclusively to them through the housing program Minha Casa Minha Vida (PMCMV) in São José dos Campos, inner city of the state of São Paulo. This dissertation describes and analyzes ethnographically the political fight’s process of the evicted families and the social movement which represented them, seeking the access to the house financing by Caixa Econômica Federal, operative agent of the housing program. Based on a fieldwork conducted through interviews and attendances to the events convened by the Movimento Urbano dos Sem-Teto (MUST), in the period between the eviction and the house’s key obtainment, I describe and analyze the uses and senses of the notions of political fight, house, memory and State by the evicted families from Pinheirinho and leaderships of the social movement in order to guarantee the access to own a house in Pinheirinho dos Palmares.